WADY WRODZONERemoval of an unstable Amplatzer occluder and surgical closure of ASD in a 10-year old girl – a case report - Wieteska, Jacek; Karolczak, Maciej; Werner, Bożena; Godlewski, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
A 10-year old girl was referred to the Second Department of Cardiac and General Paediatric Surgery, Warsaw Medical University in order to remove an unstable Amplatzer septal occluder (ASO) partially translocated towards the right atrium of the heart 15 days after ASO implantation. Surgery was performed employing cardiopulmonary bypass, the occluder was removed without any difficulties and the atrial septal defect was directly sutured. An intraoperative epicardial echocardiography confirmed the complete closure of the defect. The authors emphasize that despite two weeks time that passed from the procedure of ASO implantation, there were no surgical problems in the removal of the device.